The Wiley handbook of early childhood development programs, practices, and policies - Votruba-Drzal, Elizabeth; Dearing, Eric (Wiley Blackwell, 2017)
"A definitive reference on the thriving interdisciplinary field of applied early childhood development. The cumulative scientific knowledge on early childhood is greater than at any other point across the life span, and the formative role of early experience is well-recognized. This handbook synthesizes scientifically rigorous research from across disciplines in order to identify strategies that are most effective for promoting early childhood development. It begins with child and family approaches, moves to school and community strategies, and concludes with a discussion of the implications of broader social policies for early childhood health and development."- Resumé vydavatel
Keywords: předškolní výchova; vývoj dítěte; preschool education; child development; elektronické knihy; příručky; electronic books; handbooks and manuals